KARAKTERISTIK DADIH PROBIOTIK MENGGUNAKAN KOMBINASI LACTOBACILLUS CASEI, LACTOBACILLUS PLANTARUM, DAN BIFIDOBACTERIUM LONGUM SELAMA PENYIMPANAN - Sri Usmiati; Juniawati Juniawati (Food and Nutrition Society of Indonesia, 2011)
Some test results hedonic by ordinary people who consume the dadih in West Sumatra in 2009 on dadih made from cow's milk using Lactobacillus casei culture couldn’t be accepted because it was still too acidic than dadih from buffalo milk. One solution to reduce the sour taste is to combine the bacterial culture L. casei with other lactic acid bacteria that produce flavor relatively low acidity. The study aimed to determine the characteristics of probiotic dadih using a combination starter L. casei, L. plantarum and B. longum during storage at room temperature (ambient) and cold temperature. The study was designed using randomized block design with 6x3 factorial patterns of three groups as replication. Treatment A (combination of probiotic bacteria) that L. casei (A1), B. longum (A2), L. plantarum (A3), L. casei: L. plantarum 1:5 (A4), L. casei: B. longum 1:5 (A5) and L. casei: L. plantarum: B. longum 1:4:1 (A6), and factor B (storage conditions), namely: (B1) room temperature (27oC), and (B2) cold temperature (4-10oC). The results showed that viability and the total lactic acid bacteria in all formulas of cow's milk dadih during storage at room temperature and cold temperature of more than 106 cfu/ml which could be categorized as a probiotic products. The combination of C1L5 (L.casei: B.longum 1: 5) has the lowest acidity value and excellence in character color, flavor, and was generally preferred by the panelists. In terms of flavor and texture characteristics of cow's milk dadih with a combination of C1L5 had a level of hedonic as with other formulas. Keywords: dadih, cows milk, probiotic, storage